"Imagine all the people" : Andrija Štampar’s ideology in the context of contemporary public health initiatives = “Imagine all the people” : ideologija Andrije Štampara u kontekstu suvremenih javnozdravstvenih inicijativa - Fatović-Ferenčić, Stella (Array, 2019)
Recently, the World Health Organization launched its Universal Health Coverage initiative with the aim to improve access to quality health care on a global level, without causing financial hardship to the patients. In this paper, we will identify and analyze the ideological similarities between this influential initiative and the work of one of the founders of the WHO—Andrija Štampar (1888–1958)—whose social medicine was built of various normative, sociological and philosophical elements. Our aim is to demonstrate the crucial role of carefully erected and thought-out ideology for the success of public health programs.